Digital Mental Health Initiatives in India - Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
The burden of mental health problems is rising across the world. In South Asia region, the suicide rate is highest in India with one person dying every 40 seconds due to suicide with 16.5 suicides per 100,000 people. In 2017, around 200 million people were suffering from mental illness in India. The COVID-19 pandemic has even worsened the mental health situation in the country. People across all age groups suffered from anxiety and depression during COVID-19 lockdown. Some of the major factors that contribute to the burgeoning mental health burden are scarcity of mental health specialists particularly in rural areas,limited availability of mental health services,limited access to mental health services, stigma associated with mental illnesses and limited awareness and knowledge about mental health. The Central and state governments have taken various initiatives to deal with the mental health situation. These range from policy level initiatives like passing of Mental Health Act in 2017 to community level mental health programmes. The boom in internet access and telecommunications provide an apt opportunity for India to fill the large gap that exists in the provision of mental healthcare services.The central government has launched MANAS , a mobile application for improving mental wellbeing of citizens, Karnataka Government has launched e-Manas: Karnataka Mental Healthcare Management System and various pilot initiatives have also been taken by state governments in collaboration with private organizations. This is a concept paper based on secondary data from various national and international journals, government and private documents and websites. This paper presents an overview of mental health situation in the country and provides a detailed account of various digital platforms launched and pilot initiatives taken in India to tackle the rising burden of mental health problems. The paper also put forward some recommendations to improve the mental health situation in the country.
Keywords: 330; Mental Health; Digital; Information and Communications Technology; ICT; India